Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah dan Motivasi Siswa - Untung Teguh Budianto (Universitas Pendidikan Mandalika, 2021)
The purpose of this study is to analyze whether the application of PBL learning model to improve problem -solving skills and motivation on line and series material for students of class XI MIPA 1 SMA Negeri 1 Moga Pemalang Regency 2019/2020 school year. This class of action research consists of two cycles with stages of planning, action, observation, and reflection. Data collection was done by observation techniques, tests, and documentation. This research data analysis technique uses descriptive analysis technique. The results showed that students' problem -solving abilities improved both in cycle I and in cycle II when compared to the initial conditions. The average problem -solving ability in the initial condition is 46.36 increased to 69.88 in cycle I increased again in cycle II to 76.03. Similarly, students' learning motivation increases from cycle I to cycle II.